Assessment of chemical composition and toxicity of the essential oil of leaves and fruits of Jatropha gossypifolia L. - Juciely Moreti dos Reis; Willian Ferreira da Costa; Sandro Minguzzi; Rogério César de Lara da Silva (Semina: Ciências Exatas e Tecnológicas, 2014)
The leaves and fruits of Jatropha gossypifolia L. were evaluated for their chemical composition. The essential oil of the leaves, were obtained by hydrodistillation and the fatty material of albumen and seeds were evaluated for chemical composition and toxicity in the Artemia salina assay. The extraction yield of oil was 26.6 % 38.4 % and 0.0365 % for the seeds, leaves and albumen, respectively. The toxicity of the oil obtained from the albumen and seeds against in the Artemia salina were 74.25  0.21 g mL-1 and 78.66  0.25 g mL-1. The saponification and acidity index for the oil albumen was 165.4 mg KOH g-1 and 10%, respectively. Gas chromatography with flame ionization detection (GC-FID) was used to analyze the fatty acid profile of albumen and seeds. High percentage (35.81 %) for heptadecanoic acid (C17:0) was determined for the oil form of the seeds. Twelve compounds were identified in the essential oil obtained from the leaves by gas chromatography-mass spectrometry (GC-MS). The Kovats Index for compounds were calculated and compared to those of literature.